Prognostic impact of tace combined with sorafenib or lenvatinib followed by regorafenib in recurrent hepatocellular carcinoma after liver transplantation: a retrospective study - Zhao-dan Ye; Meng-chen Song; Al-Kalei AMA; Li Zhuang; Yan Zhang; Sheng-li Ye; He-miao Shi; Si-yi Zhong; Dan Zhu; Guo-hong Cao; Jing-feng Zhang (BMC Cancer)
Abstract Background Tumor recurrence after liver transplantation (LT) for hepatocellular carcinoma (HCC) remains a significant challenge. This study systematically evaluates the efficacy and safety of transarterial chemoembolization (TACE) combined with tyrosine kinase inhibitors (TKIs) for post-LT tumor recurrence. Methods This retrospective study included 78 patients with recurrent intrahepatic HCC after LT. Seventy patients received TACE in combination with either sorafenib or lenvatinib, followed by regorafenib. Outcomes evaluated included time to progression (TTP), post-recurrence survival (PRS), post-transplantation survival (PTS), objective response rate (ORR), and adverse events (AEs). Results The median TTP for recurrent intrahepatic HCC with combination therapy was 6 months (95% CI: 3.685–8.315), while the median PRS and PTS were 16 months (95% CI: 13.049–18.951) and 25 months (95% CI: 20.447–29.553), respectively. The ORR for intrahepatic tumors was 71.4%. AEs, including post-embolization syndrome and myelosuppression, were manageable. Conclusion TACE combined with TKIs has good efficacy and safety in the treatment of HCC recurrence post-LT and is expected to prolong survival.